Individual dental expenditure by Australian adults. (December 2013) - Teusner, DN; Brennan, DS; Gnanamanickam, ES
Abstract Background While dental service use in Australia has been extensively reported, little is known about associated costs. The aim of this article was to describe the annual individual dental expenditure of Australian adults. Methods Self‐reported service use and expenditure data were sourced from a sample of 3000 adults aged 30 to 61 years who were randomly selected from the electoral roll. Bivariate associations between total individual dental expenditure and out‐of‐pocket expenditure (fees less insurance rebate) and a range of participant characteristics were explored. Results Response rate for the baseline questionnaire was 39.4% and of these, 53.1% responded at 12‐month follow‐up. The mean total dental expenditure was $702 and mean out‐of‐pocket expenditure was $489. Toothache was associated with total dental expenditure; adults experiencing toothache had higher median expenditure ($445) than adults who hardly ever/never had toothache ($308) (p < 0.05). Dental insurance status was not associated with total expenditure, but insured had lower median out‐of‐pocket expenditure ($146) than uninsured adults ($320) (p < 0.01). Conclusions Affordability variables typically associated with access to dental care, such as insurance status, were not associated with total expenditure, while poorer oral health was associated with higher total expenditures.